2020
DOI: 10.1002/mp.14070
|View full text |Cite
|
Sign up to set email alerts
|

Online dose delivery verification in small animal image‐guided radiotherapy

Abstract: Purpose: To accomplish novel radiation treatment techniques in preclinical radiation research, small animal image-guided radiotherapy systems have been increasingly integrated into preclinical radiation research over the last decade. Although such systems have sophisticated tools (such as conebeam computed tomography-based image guidance, robotic couch, treatment planning system (TPS), and electronic portal imaging devices [EPIDs]). To our knowledge, no established technique can perform independent and online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In the study by Anvari et al., 9 the MuriPlan distributions were compared to the EPID and film distributions, and the researchers concluded that the TPS could not accurately calculate the dose in peripheral regions in which the penumbra effect was dominant. The results of the gamma analysis for a 2D comparison in a coronal plane indicated a 90% average passing rate with a global gamma criterion of 2 mm/5% for a 20 mm cone; by contrast, the coronal 2D dose distribution comparison of this study between the CAT3D TPS and the EBT3 film showed a 100% passing rate when a global gamma criterion of 1 mm/5% was applied.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study by Anvari et al., 9 the MuriPlan distributions were compared to the EPID and film distributions, and the researchers concluded that the TPS could not accurately calculate the dose in peripheral regions in which the penumbra effect was dominant. The results of the gamma analysis for a 2D comparison in a coronal plane indicated a 90% average passing rate with a global gamma criterion of 2 mm/5% for a 20 mm cone; by contrast, the coronal 2D dose distribution comparison of this study between the CAT3D TPS and the EBT3 film showed a 100% passing rate when a global gamma criterion of 1 mm/5% was applied.…”
Section: Discussionmentioning
confidence: 99%
“…for profile comparison through gamma analyses. Related to the DTA criteria, even for clinical radiation dosimetry, a 3‐mm DTA is typically applied; in this study, a 1‐mm DTA was selected because a trend toward decreasing DTA values exists due to the dimensions of the small animals irradiated in preclinical studies 4,5,9 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations